Analytical modelling of the trans-scale cutting forces in diamond cutting of polycrystalline metals considering material microstructure and size effect. (15th August 2021) - Sun, Zhanwen; Zhang, Tao; Li, Peizheng; Wang, Sujuan; To, Suet; Wang, Hailong
Highlights: The novely of the proposed force model is the consideration of microstructure and size effect. A hybrid slip-line model is proposed to capture the flow stress variation with size factor. The cutting mechanism transforms from shearing with tensile stress to ploughing with compressive stress with increasing size factor. Larger grains features smaller cutting force due to the less resistance of grain boundary on dislocaitong sliding. Abstract: In diamond cutting of polycrystalline metals, the influence of size effect and microstructure on the cutting force is prominent due to the trans-scale variation of undeformed chip thickness (UDCT) from microscale to nanoscale. This study proposes a trans-scale cutting force model for diamond cutting of polycrystalline metals with the full consideration of microstructure, material elastic recovery, size effect and round-tool-edge effect. Specifically, by corelating micro-forming theory and crystal plastic theory, a hybrid slip-line model (HSLM) is developed to determine the flow stress in the primary deformation zone, which can quantify the influence of size effect and microstructure, such as grain size, grain boundary and crystal anisotropy, on flow stress. Then, the normal cutting force and frictional cutting force are determined by analysing the stress distribution and frictional states at tool-chip interface using a tool-chip contact model. The rubbing force induced by material elastic recovery at very small UDCT is determined based on indentation theory. Through diamond cutting of polycrystalline copper with different grain sizes, it is experimentally demonstrated that the proposed HSLM can capture the cutting mechanism transformation phenomenon from shearing (tensile stress) to ploughing (compressive stress) with increasing size factor. Besides, the proposed force model has the improved estimation accuracy compared with the conventional force models developed based on Johnson-Cook constitutive equation. Graphical abstract: Image, graphical abstract